PERTUMBUHAN HUTAN TANAMAN DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) UNIVERSITAS LAMBUNG MANGKURAT - Herry Susanto; Suyanto Suyanto; Mufidah Asyari (Jurnal Sylva Scienteae, 2022)
Forest and land rehabilitation conducted at KHDTK Lambung Mangkurat University still often fails. One of the causes of this failure is the occurrence of forest fires and a lack of understanding of the suitability of selecting plant species with their plant species. This study aims to determine the types of plants that have the highest diameter and height increment and analyze the types of plants in the KHDTK area of Lambung Mangkurat University. This study uses an analysis of the growth of rehabilitation plants measuring the annual average dimension measurement (MAI) in a circle measuring plot of 0.02 ha totaling 30 measuring plots. The results of this study indicate that the Angsana species (Pterocarpus indicus) had the best diameter growth performance with an average increase of 2.29 cm/ year in 2015. Plants that had the best high growth performance were found in Mahagony species (Switenia mahagoni). with an average increase of 1.23 m/year. The types of plants contained in this study were dominated by Mahoni (Switenia mahagoni) and Angsana (Pterocarpus indicus)Rehabilitasi hutan dan lahan yang dilakukan di KHDTK Universitas Lambung Mangkurat masih sering mengalami kegagalan. Salah satu yang menjadi penyebab dari kegagalan tersebut adalah terjadinya kebakaran hutan dan kurangnya pemahaman terhadap kecocokan pemiihan jenis tanaman dengan jenis tanamhnya. Penelitian ini bertujuan untuk mengetahui jenis tanaman yang memiliki riap diameter dan tinggi terbesar dan menganalis riap jenis tanaman di wilayah KHDTK Universitas Lambung Mangkurat. Penelitian ini menggunakan analisis terhadap pertumbuhan tanaman rehabilitasi pengukuran riap dimensi rata-rata tahunan (MAI) pada plot ukur lingkaran seluas 0,02 ha sebanyak 30 plot ukur. Hasil dari penelitian ini menunjukkan jenis tanaman Angsana (Pterocarpus indicus) memiliki performa pertumbuhan diameter terbaik dengan riap rata-rata 2,29 cm/tahun pada tahun 2015. Tanaman yang memiliki performa pertambahan tinggi terbaik terdapat pada jenis Mahoni (Switenia mahagoni) dengan rata-rata riap 1,23 m/tahun. Jenis tanaman yang terdapat dalam penelitian ini didominasi oleh jenis Mahoni (Switenia mahagoni) dan Angsana (Pterocarpus indicus)